Comparison of Proprioceptive Neuromuscular Facilitation and Pilates exercises in patients with chronic low back pain: A randomized study - Ulusoy, Meltem; Iyigun, Gozde (Elsevier, 2025)
Background: Pilates and PNF exercises reduce pain, and improve function in chronic low back pain (CLBP) patients. Aim: To compare the effects of PNF and Pilates exercises on pain, body image, fear-avoidance beliefs, core stability, and balance functions in patients with CLBP. Materials and methods: Sixty CLBP patients were randomly assigned to PNF (n = 30) or Pilates (n = 30). Patients received PNF or Pilates exercise for 20 sessions over the course of 4 weeks. The outcome measures were the Numerical Pain Rating Scale, Body Cathexis Scale, Fear Avoidance Beliefs Questionnaire, Trunk Stabilization Test, and Fullerton Advanced Balance Scale. Evaluations were performed at baseline (0 weeks) and the end of treatment (4 weeks). Results: The Pilates group showed more significant improvements in core stability (F = 8.647, p = 0.005, eta 2 = 0.134) than the PNF group. In both groups, the pain was reduced, and fear-avoidance behaviors were decreased. Improvements in balance were observed in each group. Only the Pilates group improved in terms of body image (p = 0.050, r = 0.35) and core stability (p = 0.002, r = 0.57). Conclusion: Patients with CLBP who participated in either Pilates or PNF exercises showed similar improvements in pain, body image, fear-avoidance beliefs, and balance, while Pilates exercises were more effective in improving core stability. CLBP patients in both groups showed improvements in pain severity, fear-avoidance beliefs, and balance. Only the Pilates group improved in body image and core stability. Pilates, a mind-body technique that encourages movement control and self-awareness, may offer additional advantages over PNF.
Keywords: CLBP; Pilates; PNF